PENGARUH RETURN ON EQUITY DAN TOTAL ASET TERHADAP PRICE BOOK VALUE PADA PERUSAHAAN PERTAMBANGAN DENGAN DEBT TO EQUITY RATIO SEBAGAI VARIABEL INTERVENING - Astohar, Astohar; Sumiyanti, Tri (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
The purpose of this study is to develop structural models of factorsthat affect the value of the company. Company value is influenced by theprofitability and size of the company directly or in the intervening capitalstructure. The selected research object is in mining company at IndonesiaStock Exchange in period 2010 to 2015.The sample size required for thisstudy was initially as many as 42 companies. After screening there are 29companies that can be used or 174 observations with sampling techniqueusing purposive non random sampling. The analysis tool used is normalitytest, deviation of classical assumption, data fit test, regression equation test,hypothesis test and coefficient of determination. Sobel test test in this researchis also conducted to test whether intervening variable is capital structure.The results showed that the capital structure (debt to equity ratio) andprofitability (return on equity) proved to have a positive and significanteffect on the value of the company (price book to value). Profitability (returnon equity) proved to negatively and significantly affect the capital structure(debt to equity ratio). The size of the firm (size) proved to have a positiveand significant influence on the structure of capital (debt to equity ratio).The size of the firm (size) proved to have a negative effect is not significantto the value of the company (price book value). The capital structure (debt toequity ratio) proves to be a mediating variable between return on equity andfirm size to firm value